Congenital Portosystemic Shunts: Current Diagnosis and Management. Issue 5 (May 2019) - McLin, Valérie A.; Franchi Abella, Stephanie; Debray, Dominique; Guérin, Florent; Beghetti, Maurice; Savale, Laurent; Wildhaber, Barbara E.; Gonzales, Emmanuel
Abstract : ABSTRACT: Congenital portosystemic shunts are increasingly recognized in several settings and at any age. The following are some of the most common presentations: prenatal ultrasound, neonatal cholestasis, incidental finding on abdominal imaging, or systemic complications such as unexplained cardiopulmonary or neurological disease, or the presence of liver nodules in a noncirrhotic liver. The purpose of the present review is to summarize clinical presentation and current recommendations for management, and highlight areas of future research. Illustrative examples from the veterinary literature complement our current lack of knowledge of this rare malformation often masquerading as a multisystem disease.